Problem-Solving Ability through Flipped-Problem Based Learning on Elasticity Materials for High School Student - Anggraeni, Dwi Astuti; Hakim, Abdul; Sulaeman, Nurul Fitriyah (Kasuari: Physics Education Journal (KPEJ), 2023)
This study aims to enhance problem-solving ability through Flipped-Problem Based Learning model on elasticity material for high school students. The type of research used is quantitative research with a one-group pretest-posttest design. The data collection technique uses Polya indicators, that is understanding the problem, devising a plan, carrying out the plan, and looking back. The assessment was carried out with help of the Minnesota Assessment of Problem Solving (MAPS) rubric. Data were analyzed using N-gain and Wilcoxon Signed Rank tests with an N-Gain score of 0.55 which was included in the medium category. The results of the Wilcoxon Signed Rank test showed a p-value of 0.00 with a significance of 0.05 which stated that there was a significant difference between students' problem-solving abilities after the Flipped-Problem Based Learning model was applied. The results showed that there was an increase in the problem-solving ability of students